CRIME IN THE TIME OF THE PLAGUE: FAKE NEWS PANDEMIC AND THE CHALLENGES TO LAW-ENFORCEMENT AND INTELLIGENCE COMMUNITY - GRADOŃ, KACPER (Society Register, 2020)
The Paper explores the problem of fake news and disinformation campaigns in the turmoil era of the COVID-19 coronavirus pandemic. The Author addresses the problem from the perspective of Crime Science, identifying the actual and potential impact of fake news propagation on both the social fabric and the work of the law-enforcement and security services. The Author covers various vectors of disinformation campaigns and offers the overview of challenges associated with the use of deep fakes and the abuse of Artificial Intelligence, Machine-, Deep- and Reinforcement-Learning technologies. The Paper provides the outline of preventive strategies that might be used to mitigate the consequences of fake news proliferation, including the introduction of counter-narratives and the use of AI as countermeasure available to the law-enforcement and public safety agencies. The Author also highlights other threats and forms of crime leveraging the pandemic crisis. As the Paper deals with the current and rapidly evolving phenomenon, it is based on qualitative research and uses the most up-to-date, reliable open-source information, including the Web-based material.